Evolving friendship? Essential changes, from social networks to artificial companions - Bosch, Magdalena; Fernandez-Borsot, Gabriel; Miró I. Comas, Abel; Figa Vaello, Jaume (Social network analysis and mining, 2022)
Although the possibility of virtue friendship (friendship according to the Aristotelian ideal) has been studied both in online friendship and in friendship with artificial companions (ACs), there is one essential aspect that has been neglected or overlooked: the change in the subject with whom one becomes a friend. Is friendship changing in our society? Are the new ways of communication and the incipient presence of artificial companions (robots or software aimed at triggering emotional bonding experiences in the user) making any significant change in friendship? The question of the subject is the common problem of the two ways of friendship under study. From the point of view of the subject, these two ways present significant changes compared to traditional in-person friendship. In the case of online friendship, the change is the means of communication. Though this is not a fundamental change, it impacts and constraints the relational modes in such a way that the other becomes a “diminished other”. On the other hand, friendship with ACs means that the “friend” is an AI system designed to establish a relationship with the user that seamlessly emulates human friendship. Here the change is the subject itself. And here comes the question: Are there any essential conditions for the subject friend as a subject? Is it enough that a relationship produces a satisfying feeling of engagement for an individual? Is the ontological status of the other with whom the friendship is established decisive, or can the analyses be focused only on the experience the relationship produces in the individual? The article provides key concepts to undertake an ontological evaluation of these questions. Essential Aristotelian concepts that have not been considered sufficiently when discussing this topic are also presented: friendship “for the friend’s sake”, equality and interiority.